Perilaku Pemilih dalam Pemilihan Presiden dan Wakil Presiden Tahun 2024 di Provinsi Sulawesi Tengah - Indama, Intje Supriadi (Jurnal Ilmiah Widya Sosiopolitika; Vol 7 No 1 (2025): ISU-ISU SOSIAL DAN POLITIK, 2025)
Voter behavior plays a criticVoter behavior plays a critical role in shaping electoral outcomes and reflects the socio-political dynamics within a region. This study aims to analyze voter behavior in the 2024 Presidential and Vice Presidential Election in Central Sulawesi Province, Indonesia. The research adopts a descriptive quantitative approach using secondary data sourced from the General Elections Commission (Komisi Pemilihan Umum), the Central Statistics Agency (Badan Pusat Statistik), and relevant voter behavior surveys. The results indicate that voter preferences in Central Sulawesi are primarily influenced by emotional attachment to political figures, party affiliation, local issues, and the impact of social media. A notable finding of this study is the significant role of local cultural identity and regional sentiment in shaping political choices, highlighting the growing relevance of socio-cultural considerations in electoral decisions. These findings suggest that understanding voter behavior in the region requires both cultural and sociological perspectives. The study offers strategic insights for political parties and election organizers in designing more effective political communication strategiesl role in shaping electoral outcomes and reflects the socio-political dynamics within a region. This study aims to analyze voter behavior in the 2024 Presidential and Vice Presidential Election in Central Sulawesi Province, Indonesia. The research adopts a descriptive quantitative approach using secondary data sourced from the General Elections Commission (Komisi Pemilihan Umum) , the Central Statistics Agency (Badan Pusat Statistik) , and relevant voter behavior surveys. The results indicate that voter preferences in Central Sulawesi are primarily influenced by emotional attachment to political figures, party affiliation, local issues, and the impact of social media. A notable finding of this study is the significant role of local cultural identity and regional sentiment in shaping political choices, highlighting the growing relevance of socio-cultural considerations in electoral decisions. These findings suggest that understanding voter behavior in the region requires both cultural and sociological perspectives. The study offers strategic insights for political parties and election organizers in designing more effective political communication strategies.